Lectura infantil y su incidencia en el proceso enseñanza aprendizaje de la Escuela de educación básica Región Litoral, Periodo 2014-2015, Guía didáctica. - Coello Vera, Gueyda (2015)
In the process of teaching and learning, reading becomes the most significant category, because to achieve reading skills, the student begins to discover the written knowledge through various sources. Dialogic reading, the meaning of words, understanding of thought and learning are discovered in an intense and delightful way with endless successive experiences. This research focuses on children's reading and their impact on the teaching process in the School of Basic Education "in riverside," Quevedo canton. In developing it could detect little use that teachers give reading in their academic work and low reading level of students and how these factors affect academic performance. Therefore the application of dynamic and innovative to make reading a valuable educational resource to strengthen learning techniques is necessary. With this research is to improve the teaching - learning through the use of childhood reading, to do an educational guide that will benefit the entire school community is presented. The use of childhood reading in the development of learning will allow students to achieve basic education intellectual abilities in different dimensions and expressions of language. The budget for this research was $ US $ 434,00.